Analisis Sistem Pengendalian Manajemen Dalam Mendukung Kinerja Perusahaan - Ambarita, Dena Christin; Trinadia, Windi; Darma, Jufri (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the role of Management Control Systems (MCS) in supporting the improvement of company performance. The method used is normative research through a literature review that refers to both classical theories and recent studies. Anthony & Govindarajan (2011) state that MCS is a critical process to ensure that organizational strategies are implemented effectively and efficiently. Kaplan & Norton (1996) emphasize that company performance should not only be measured by financial indicators but also by non-financial ones through the Balanced Scorecard framework. The findings of the review indicate that the integrated application of MCS through strategic planning, budgetary control, and performance evaluation can enhance operational efficiency, accountability, and corporate competitiveness (Indriani & Nurdin, 2020; Merchant, 2018). However, common challenges faced by companies include weak reporting systems, limited use of information technology, and organizational cultures that are less adaptive to change (Chowdhury, 2022). Therefore, companies need to strengthen the implementation of MCS by leveraging digital innovation, enhancing human resource competencies, and consistently applying good corporate governance principles to maintain performance and business sustainability.